Diagnosa Penyakit dengan Gejala Demam pada Manusia Berbasis Mobile : Knowledge Based System - John Adler (Komputika : Jurnal Sistem Komputer, 2017)
Abstract - Fever is a disease caused by health problems by bacteria, viruses, or tissue system abnormalities in human organs at body temperatures exceeding 370 C, also influenced by the environment in the form of weather. It can also be a resistance of white blood cells or human antibodies with viruses or bacteria. Symptoms of this disease can endanger a person's life if not taken seriously. For this reason, you need basic knowledge in detecting fever about symptoms and what types of fever a person has. Although later a small portion of these symptoms are similar to other diseases, so we are always wrong in predicting an illness. In this research a program that is accurate in humans is designed that can identify fever, is able to detect the types of diseases that might be infected by someone with early symptoms of fever, and is able to classify symptoms. Then using the Fuzzy Logic method can be measured the level of probability of each disease with the initial symptoms of fever in each disease. So that from this program several types of diseases will be shown. Mobile device applications in the form of smartphones that are based on Android, so that programs that have been packaged can be used by the wider community. The results of this study can be concluded that the disease can be detected as many as 19 types of diseases and 56 symptoms. By using the black box method, 82.4% of the results of the survey conducted at Puskesmas Tubagus Ismail Bawah, Hasan Sadikin Hospital, Students, Community, Pharmacists and doctors will be produced. So there is no consultation with the doctor directly with these initial symptoms, because the program created has been very helpful for citizens in diagnosing the disease. Keywords: Diagnose, Fever, Mobile, Fuzzy Logic